2018
DOI: 10.1038/modpathol.2017.126
|View full text |Cite
|
Sign up to set email alerts
|

Composite analysis of immunological and metabolic markers defines novel subtypes of triple negative breast cancer

Abstract: Cancer biology is influenced by the tumor microenvironment that impacts on disease prognosis and therapeutic intervention. The inter-relationship of tumor infiltrating lymphocytes, immune response regulators, and a glycolytic tumor environment was evaluated in a cohort of 183 largely consecutive patients with triple negative breast cancer diagnosis. High levels of tumor infiltrating lymphocytes were associated with improved survival of triple negative breast cancer cases. However, elevated levels of PD-L1, CD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 57 publications
(61 reference statements)
6
42
2
Order By: Relevance
“…Magnification: × 100 [34]. Finally, the levels of immune marker staining seen in our MBC samples (lower CD8, higher CD163, and higher PD-L1) is comparable to data from previous publications using TNBC samples [25,28]. The prognosis of MBC, when compared to TNBC, has traditionally been known to be worse, but survival outcomes have varied across numerous studies.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Magnification: × 100 [34]. Finally, the levels of immune marker staining seen in our MBC samples (lower CD8, higher CD163, and higher PD-L1) is comparable to data from previous publications using TNBC samples [25,28]. The prognosis of MBC, when compared to TNBC, has traditionally been known to be worse, but survival outcomes have varied across numerous studies.…”
Section: Discussionsupporting
confidence: 83%
“…Figure 3 shows images of the different immune markers and PD-L1 expressions in two metaplastic breast carcinomas. The immune marker profile of our MBC samples is analogous to those generated from TNBC samples in previous studies, which demonstrated associations between lower CD8, higher CD163, higher PD-L1 staining and worse prognosis [25,28].…”
Section: Immune Checkpoint Marker Expressionsupporting
confidence: 58%
See 1 more Smart Citation
“…PD‐L1 expression evaluated by IHC on untreated primary BC has been associated with both better and poorer clinical outcome. In particular, several authors reported poorer disease‐free survival (DFS)/recurrence‐free survival (RFS) and/or overall survival (OS) in cases of higher PD‐L1 expression on primary BC , especially in the TN subtype . These results seems to be consistent with the previously mentioned correlation between PD‐L1 expression and unfavorable clinicopathological BC features, thus possibly indicating that PD‐L1 expression may be part of the immune evasion process taking place in the context of tumor microenvironment .…”
Section: Methodssupporting
confidence: 77%
“…Monocarboxylic acid transporter 4 (SLC16A3/MCT4) is one of the membrane protein stubs in cells that is structurally able to output lactic and pyruvic acids and affect the acidity of the tumor microenvironments. [15][16][17] High expression of MCT4 has been reported to be a biomarker in various types of tumors, [18][19][20][21][22][23][24] which makes it an appealing therapeutic target in cancers. The blockade of MCT4 expression has been shown to represent a novel treatment target in glioblastoma, large B-cell lymphoma, and multiple myeloma.…”
Section: Introductionmentioning
confidence: 99%